Prostate cancer - risk factors and prevention strategies - Rybak, Jakub; Magiera, Barbara; Magiera, Karol (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Prostate cancer is the second most frequent malignancy in men worldwide. The aim of this study is to analyze the key modifiable and non-modifiable risk factors associated with the development of prostate cancer and to discuss existing prevention strategies. Materials and methods: A literature review was conducted using the "PubMed" database with the keywords "prostate cancer", "prostate cancer risk factors", "prostate cancer prevention”. State of knowledge: Prostate cancer risk factors can be divided into two groups: modifiable and non-modifiable. Modifiable risk factors include: diet, infections and alcohol use. Non-modifiable risk factors include: age, race, genetic factors, and family history. Chemoprevention plays an important role in the prevention of prostate cancer. Summary: Despite the fact that prostate cancer remains a significant challenge for current medicine, the development of preventive methods in recent years gives hope for reducing mortality associated with the disease. Research is still being conducted to identify prostate cancer risk factors and to improve methods of primary and secondary prevention.